Judiciarização dos conflitos: o uso da Lei Maria da Penha - Fraga, Rosana Vargas (2013)
His work presents the use of the Maria da Penha Law by women who carry case record at the station to protect women in the city of Santa Maria. Legal bodies such as police protection to woman, symbolized a space for the implementation of the law and the record of the police report the first instrument for this process. The opportunity that women achieved with the creation of the law to denounce opened precedent for interpretations and understandings of what the law actually punishes and on the situations which have led to make the case record for punishment of domestic violence through criminalization, on the other hand, do not have other forms of conflict resolution which are not insusceptible of law, but are made by women in the police station.